2018
DOI: 10.1038/s41598-018-30887-8
|View full text |Cite
|
Sign up to set email alerts
|

α-Gal on the protein surface affects uptake and degradation in immature monocyte derived dendritic cells

Abstract: Red meat allergy is characterized by an IgE response against the carbohydrate galactose-α-1,3-galactose (α-Gal), which is abundantly expressed on glycoproteins from non-primate mammals. The mechanisms of how α-Gal is processed and presented to the immune system to initiate an allergic reaction are still unknown. The aim of this study was to reveal whether the presence of α-Gal epitopes on the protein surface influence antigen uptake and processing in immature monocyte-derived dendritic cells (iMDDCs). Immature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The way of internalization and processing of antigens determines whether an antigen is considered as harmless or as dangerous by the body. Ristivojević et al (124) showed in in vitro experiments in immature monocyte-derived dendritic cells (iMDDCs) that the uptake of bovine serum albumin (BSA) increased substantially when the protein was glycosylated and carried α-Gal moieties on the surface. Furthermore, the presence of α-Gal also affected the degradation pathway of BSA since α-Gal carrying BSA was slower degraded than BSA without α-Gal (124).…”
Section: Role Of Human Immune Cells In Agsmentioning
confidence: 99%
See 1 more Smart Citation
“…The way of internalization and processing of antigens determines whether an antigen is considered as harmless or as dangerous by the body. Ristivojević et al (124) showed in in vitro experiments in immature monocyte-derived dendritic cells (iMDDCs) that the uptake of bovine serum albumin (BSA) increased substantially when the protein was glycosylated and carried α-Gal moieties on the surface. Furthermore, the presence of α-Gal also affected the degradation pathway of BSA since α-Gal carrying BSA was slower degraded than BSA without α-Gal (124).…”
Section: Role Of Human Immune Cells In Agsmentioning
confidence: 99%
“…Ristivojević et al (124) showed in in vitro experiments in immature monocyte-derived dendritic cells (iMDDCs) that the uptake of bovine serum albumin (BSA) increased substantially when the protein was glycosylated and carried α-Gal moieties on the surface. Furthermore, the presence of α-Gal also affected the degradation pathway of BSA since α-Gal carrying BSA was slower degraded than BSA without α-Gal (124). This suggests that α-Gal, but not the protein carrying the oligosaccharide, is recognized by the DCs as an antigen and affects the uptake and processing of the protein.…”
Section: Role Of Human Immune Cells In Agsmentioning
confidence: 99%
“…8 Additionally, the processing and degradation of alpha-gal can be delayed when present on the surface of proteins, with the latter perhaps reducing the rapid availability of suitably exposed IgE binding epitopes. 9 More recently, as our understanding of alpha-gal allergy has improved, the link between this and other tick bite mediated pathology has been explored. Tjernberg et al investigated the relationship between IgE antibodies to alpha-gal and the prevalence of Lyme borreilosis in 518 healthy blood donors in Sweden.…”
Section: Discussionmentioning
confidence: 99%
“…The several-hour delay was originally thought to be caused by ineffective dendritic cell (DC) function. A recent study, however, showed that the presence of α-Gal on modified proteins actually increases the efficiency of antigen uptake 20 . The authors further suggest that α-Gal may protect proteins from degradation, thereby slowing the process of major histocompatibility complex (MHC) presentation and antigen recognition 20 .…”
Section: Ige and Ticksmentioning
confidence: 99%